2023
DOI: 10.1007/s11356-023-26260-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of curcumin versus nano-curcumin on histological, immunohistochemical expression, histomorphometric, and biochemical changes to pancreatic beta cells and lipid profile of streptozocin induced diabetes in male Sprague–Dawley rats

Abstract: Diabetes mellitus is a worldwide problem characterized by hyperglycemia as well as the damage of the microscopic structure of the beta cells of Langerhans pancreatic islets. In the present study, the histological, immunohistochemical, morphometric, and biochemical alterations to pancreatic beta cells in streptozocin (STZ)-induced diabetes were assessed in rats treated with curcumin (CU) (100 mg/kg/day) or nano-curcumin (nCU) (100 mg/kg/day) for 1 month. Twenty-four adult male Wistar albino rats were distribute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Interestingly, NCur was superior to Cur in promoting insulin levels, antioxidant enzyme activities (SOD, GSH) and PDX1 expression while reducing pancreatic caspase 3 in the STZ-induced diabetic rat model. 63 In the present study, we further demonstrated that NCur significantly suppressed mitochondrial ROS production, mitochondrial fission, mitophagy, and inflammation in ECs exposed to HG and PM. Furthermore, animal experiments using STZ-induced diabetic mice exposed to PM confirmed the cell-based findings.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, NCur was superior to Cur in promoting insulin levels, antioxidant enzyme activities (SOD, GSH) and PDX1 expression while reducing pancreatic caspase 3 in the STZ-induced diabetic rat model. 63 In the present study, we further demonstrated that NCur significantly suppressed mitochondrial ROS production, mitochondrial fission, mitophagy, and inflammation in ECs exposed to HG and PM. Furthermore, animal experiments using STZ-induced diabetic mice exposed to PM confirmed the cell-based findings.…”
Section: Discussionsupporting
confidence: 75%